The Impact of Length of the School Year on Student Performance and Earnings: Evidence from the German Short School Years - Jörn-Steffen Pischke (Institute for the Study of Labor (IZA), 2003)
This paper investigates how changing the length of school year, leaving the basic curriculum unchanged, affects learning and subsequent earnings. I use variation introduced by the West-German short school years in 1966-67, which exposed some students to a total of about two thirds of a year less of schooling while enrolled. I show that the short school years led indeed to shorter schooling for affected students. Using comparisons across cohorts, states, and secondary school tracks, I find that the short school years increased grade repetition in primary school, but had no adverse effect on the number of students attending the highest secondary school track or earnings later in life.
Keywords: J31; J24; 330; human capital; returns to schooling; length of school year; term length; grade repetition; tracking; Schule; Unterricht; Dauer; Bildungsertrag; Bildungsverhalten; Deutschland